De-marketing Tobacco Through Price Changes and Consumer Attempts Quit Smoking - Inness, Michelle (Journal of business ethics, 2008)
Using panel data from three Canadian provinces, this article examines the relationship between the de-marketing of tobacco products through provincial-level price increases and consumers’ attempts to quit smoking as measured by the uptake of tobacco replacement therapies. We ground our hypotheses in the rational addiction model and the theory of planned behavior. Our analyses suggest a positive, one-month lagged effect of a price increase of tobacco products on the uptake of tobacco replacement therapies. This effect dissipates 3 months later, suggesting that there is a critical period for aggressive de-marketing of tobacco products. We discuss the implications of these results for theory and future research into de-marketing harmful consumer products.